The clinical dilemma for acute scrotum in paediatrics: A rare etiology - Sayanthan, B.; Vaishnavi, S. (Elsevier, 2022)
The acute scrotum is a clinical scenario and it is considered as a paediatric urological emergency with acute onset of pain and swelling of the scrotum with its contents. It is quite challenging for the clinician to make a precise differential diagnosis because it has various etiologies, overlapping clinical presentations and the extreme tenderness over the area that makes clinical examination difficult. Torsion of the testis is a surgical emergency condition with prevalence of acute scrotal disease in the paediatric population that occurs due to twisting the spermatic cord. This case provides a clue to clinician for managing with the unique situation of parasitic disease as an acute scrotum.
Keywords: Acute scrotum; Paediatric; Urological emergency; Parasitic granuloma; Case report